Diversity of fish species in the Sibam River, Pekanbaru, Riau - Lola C.C. Hatauruk; Chaidir P. Pulungan; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Sibam River is one of black water rivers in Riau. It was inhabit by numerous fish species, but information on these fish is almost none. To understand the diversity of fish in that river, a study has been conducted from May to July 2015. There were 5 sampling areas, in the upstream (St I and II), middle (St III and IV) and downstream (St V) of the river. The fish was sampled using net (mesh size 0.5 cm inch), scoop net (mesh size 0.5 cm) and electrofishing. Data were then analyzed to find out the diversity (H’), evenness (E) and dominance (C) indexes. The fish sampled were identified based on Saanin (1984) and Kottelat (1993). The fish species present were consisted of 5 order, 16 families, 30 genus, and 41 species. The highest fish abundance was found in the ST III, and the most common species was Bagrichthys macracanthus. Osteochilus hasselti and Rasbora argyrotaenia were distributed evenly along the river, as they were found in each sampling area (Fi 100%). In the St I, II and V, the Diversity index values were high, while those in the St III and IV were medium. In all study areas the uniformity index values were high, while the dominance indexes were low.Keywords: Fish Diversity, Sibam River, Pekanbaru, Riau